Inverted signaling by bacterial chemotaxis receptors - Shuangyu Bi; Fan Jin; Victor Sourjik (Nature Communications, 2018)
Bacteria use chemotaxis receptors to perceive environmental factors. Here, the authors show that mutations in a chemotaxis receptor can invert the sensory response, e.g. from attractant to repellent, and use these mutants to map regions that enable the receptor to sense multiple environmental factors.